An approach for modeling non-ageing linear viscoelastic composites with general periodicity. (1st September 2019) - Cruz-González, O.L.; Guinovart-Sanjuán, D.; Rodríguez-Ramos, R.; Bravo-Castillero, J.; Guinovart-Díaz, R.; Merodio, J.; Penta, R.; Otero, José A.; Dumont, S.; Lebon, F.; Sabina, F.J.
Abstract: The present work deals with the modeling of non-ageing linear viscoelastic composite materials and quasi-periodic microstructure. The stratified functions and the curvilinear coordinates play an important role in the design of different geometrical shapes. The main objective focuses on the application of two-scales Asymptotic Homogenization Method (AHM) to obtain the overall behavior of the viscoelastic composite materials. Although the whole process is based on the analysis of laminated configurations, a multi-step homogenization scheme to estimate the effective properties of a structure reinforced with long rectangular fibers and wavy effects is used. The associated local problems, the homogenized problem and the analytical expressions for the effective coefficients are obtained by using the correspondence principle and the Laplace-Carson transform. Also, the interconnection between the effective relaxation modulus and the effective creep compliance is performed. Finally, the inversion to the original temporal space is calculated. Some comparisons between the proposed approach and Finite Elements Method (FEM) results are displayed.